OFFENSIVE LANGUAGES IN BAD BOYS 2 - I Made Astu Mahayana (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2017)
This research focuses on the forms of offensive language and the functions in social context found in Bad Boys 2 movie. The writer applied some methods, such as data source, data collection, and data analysis. The data source of this research was Bad Boys 2 movie’s script. The movie is chosen because there are many expressions consisting of offensive language. The library research technique was used in collecting the data by quoting the sentences that support the topic of discussion. In analyzing the data, the writer applied the offensive language theory proposed by Timothy Jay (1992) in his book entitled Cursing in America and the theory of speech function proposed by Janet Holmes (1992) in his book entitled An Introduction to Sociolinguistics as the main theory. The analysis in this paper was also supported by other references which are related to this topic. The result of this research shows that there are only eight forms found in the data source. They are cursing, profanity, taboo, obscenity, vulgarity, slang, epithets, insult and slur.